(untitled) (AYUSHDHARA, 2025)
Diterpene glycosides found in Stevia rebaudiana leaves provide food items a sweet flavour but no calories. For generations, the indigenous Guarani Indians of South America have used stevia as a sweetener to offset the harsh flavour of a variety of medications and drinks. This plant produces diterpene glycosides, which are used as sweeteners in foods and drinks since they are 100–300 times sweeter than sucrose. They have no shelf-life restrictions and stay stable in food items over a broad range of pH and temperature conditions during processing. These glycosides are appropriate for diabetics and obese people since they do not cause a glycaemic reaction when consumed. India has a large potential market for this natural sweetener due to the country’s rising rates of obesity and diabetes.